The Effect of 17b-Estradiol on the Development of Modified Hemal Spines in Early–Life Stage Gambusia holbrooki - Rawson, Christopher; Lim, R.; Warne, M.; doyle, C. (Springer-Verlag, 2006)
The morphologic development of the gonopodium of male mosquitofish, Gambusia holbrooki, is essential for proper reproductive function and has previously been used as a biomarker for the presence of endocrine-disrupting chemicals (EDCs) in freshwater systems. The development of the gonopodium is accompanied by the modification of the hemal spines on the 14th, 15th, and 16th vertebrae. These form an anchor for the movement of the gonopodium, and their normal development is therefore critical. This development is under hormonal control. It has been hypothesized that the modification of the hemal spines may be used as an end point for understanding the effects of exposure of early–life stage fish to EDCs and to add to the understanding of the differential sensitivities of different life stages. Larval fish were exposed to concentrations (0, 20, 100, and 500 ng/L) of 17b-estradiol (E2) in two experiments using a flow-through system for 8 and 12 weeks. There was a general delay in the development of the three hemal spines when exposed to high concentrations of E2. However, this delay was not observed for all end points on a particular spine nor across all spines. Fish examined at 8 weeks postpartum showed a more extensive delay at high concentrations than those examined at 12 weeks postpartum, suggesting that later in the life cycle, high levels of exogenous E2 may be overcome by increasing levels of endogenous androgen. There was a decrease in the number of phenotypic male fish present in the 500-ng/L treatment at 12 weeks postpartum and an apparent decrease in the degree of sexual differentiation at high levels of E2 exposure. The results suggest that effects of EDC exposure begin very early in a fishs life cycle.